PENGARUH PELATIHAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI (PADA DINAS KESEHAN PROVISINSI LAMPUNG TAHUN PERIODE 2022) - Yuliana, Suci (Jurnal Enterpreneur dan Bisnis (JEBI), 2024)
This study aims to determine the effect of job training on employee work productivity with motivation as a mediating variable. This study took 78 samples with a population of 363 employees. This research method uses quantitative research, data collection techniques by conducting observations with questionnaire media. The analysis method uses Validity Test, Reliability Test, Normality Test, Heteroscedasticity Test, Linearity Test, Simple Regression Test and Part Analysis (Path Analysis). The results of this study indicate that the training variable has a significant effect on the motivation variable because it has a t value of 13.331 t table 1.992, the training variable has a significant influence on the productivity variable because it has a t count value of 3.329 t table 1.992, the motivation variable has a significant influence. significant on productivity because it has a t value of 2.829 t table 1.992 and the training variable has no significant indirect effect on the productivity variable through motivation as an Intervening variable, which is 0.837 x 0.034 = 0.028. Based on the decision making, the result of the indirect effect is 0.028 from the direceffect of 0.837, then Ha is rejected and H0 is accepted.